Preservation injury of jejunal grafts and its modulation by custodiol and university of wisconsin perfusion solutions in wistar rats - Baláz, P; Matia, I; Jackanin, S; Rybárová, Emília; Kron, I; Pomfy, M; Fronek, J; Ryska, M (European surgical research. Europaische chirurgische Forschung. Recherches chirurgicales europeennes, 2004)
BACKGROUND: The two preservation solutions most commonly used in human transplantation surgery are University of Wisconsin (UW) and Custodiol (histidine-tryptophan-ketoglutarate; HTK). The aim of our study was to compare the protective effect of UW and HTK solutions on preservation-induced injury of jejunal grafts, as evaluated by the histological changes (semiquantitative method) and small bowel mucosal serotonin levels (as a possible new quantitative method). METHODS: Male Wistar rats (n = 50) weighing 316 +/- 52 g were divided into two main groups according to which preservation solution was used, i.e. UW (n = 25) or HTK (n = 25), and each of these groups was divided into five subgroups according to cold ischemic time (0, 1, 6, 9 and 12 h). Jejunal mucosa biopsy specimens were obtained to determine the serotonin concentration in mucosa and for standard light histology. To grade histological changes in mucosa, Park's small bowel injury grading system was used. RESULTS: Histological examination revealed that injury increased with cold ischemic time in the UW as well as in the HTK group, and there were no significant differences in injury between the two groups, except for the 6-hour cold ischemic period (p < 0.05), when HTK-preserved grafts showed a lower degree of injury (0.97 +/- 0.41) compared with UW-preserved grafts (1.25 +/- 0.39). The mucosal serotonin concentration decreased with cold ischemic time in both groups, and there were significant differences (p < 0.05) in concentrations between the groups after 9 and 12 h of cold ischemia. A significantly higher concentration was measured in grafts preserved in UW solution at these time points. CONCLUSION: The concentration of mucosal serotonin in rat small bowel grafts preserved for 9 and 12 h in UW preservation solution was significantly higher than that in HTK solution. These findings indicate a better protective effect of UW solution on small bowel injury after 9 h of cold ischemia.
Keywords: Insulin; Potassium Chloride; adenosin; mannitol; Glucose; Male; chlorid draselný; Rats, Wistar; inzulin; serotonin; rafinosa; Mannitol; střevní sliznice; Procaine; glukosa; mužské pohlaví; potkani Wistar; Organ Preservation Solutions; reperfuzní poškození; jejunum; krysa rodu Rattus; glutathion; Animals; nízká teplota; roztoky pro uchovávání orgánů; zvířata; Intestinal Mucosa; Jejunum; Cold Temperature; Rats; Reperfusion Injury; Glutathione; Adenosine; prokain; Serotonin; alopurinol; Raffinose; Allopurinol